Secondary metabolites in grapevine: crosstalk of transcriptional, metabolic and hormonal signals controlling stress defence responses in berries and vegetative organs - Ferrandino, Alessandra; Pagliarani, Chiara; Pérez-Álvarez, Eva Pilar (Frontiers in Plant Science, 2023)
Abiotic stresses, such as temperature, heat waves, water limitation, solar radiation and the increase in atmospheric CO2 concentration, significantly influence the accumulation of secondary metabolites in grapevine berries at different developmental stages, and in vegetative organs. Transcriptional reprogramming, miRNAs, epigenetic marks and hormonal crosstalk regulate the secondary metabolism of berries, mainly the accumulation of phenylpropanoids and of volatile organic compounds (VOCs). Currently, the biological mechanisms that control the plastic response of grapevine cultivars to environmental stress or that occur during berry ripening have been extensively studied in many world viticultural areas, in different cultivars and in vines grown under various agronomic managements. A novel frontier in the study of these mechanisms is the involvement of miRNAs whose target transcripts encode enzymes of the flavonoid biosynthetic pathway. Some miRNA-mediated regulatory cascades post-transcriptionally control key MYB transcription factors, showing, for example, a role in influencing the anthocyanin accumulation in response to UV-B light during berry ripening. DNA methylation profiles partially affect the berry transcriptome plasticity of different grapevine cultivars, contributing to the modulation of berry qualitative traits. Numerous hormones (such as abscisic and jasmonic acids, strigolactones, gibberellins, auxins, cytokinins and ethylene) are involved in triggering the vine response to abiotic and biotic stress factors. Through specific signaling cascades, hormones mediate the accumulation of antioxidants that contribute to the quality of the berry and that intervene in the grapevine defense processes, highlighting that the grapevine response to stressors can be similar in different grapevine organs. However, the expression of genes responsible for hormone biosynthesis is largely modulated by stress conditions, thus resulting in the numerous interactions between grapevine and the surrounding environment.